تعليم اللغة العربية على أساس الذكاءات المتعددة بمؤسسة الدورية مركز العربية بباري كديري - Admi, Letty Maulida (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2020)
The purpose this research is to describe Arabic learning based on linguistic intelligence, use of methods on kinesthetic intelligence, and use media on visual and musical intelligence in learning Arabic in "Markaz Arabiyah" course institute in the I'dad and Syarqi awal programs. This research apply a qualitatif design using case study methods. Data collection techniques include interviews, observations and documentation. Then the data analysis technique in this study used the concept of Miles and Huberman who stated that activities in the analysis include data reduction, data display and data verification.  The results of this study indicate that: (1) learning Arabic at the Pare Kediri Arabiyah Markaz Course Institute based on linguistic intelligence is  speaking, debate, developing vocabulary, istima ’, telling stories,  brainstorming, weekly speaking, weekly speeches, compulsory boarding speeches, daily expressions, weekly brainstorming, vocabulary development and language improvement. (2) demonstration as a method of learning Arabic has been used in learning Muhadatsah on the map chapter, playing eat bulaga, playing puppets, on extracurricular activities in dhomir material. (3) pictures and music become a learning media that is suitable for students who have visual intelligence and musical. The media image is used during ta'birat learning, speaking extracurricular activities, eat bulaga games in ta’birat learning and in the drama liqa 'usbu'. While music is used as a learning medium in speaking learning in the syarqi awal program and joint singing activities when liqa'usbu '.